Beyond the Deficit Model: The Ambassador Approach to Public Engagement. (29th March 2019) - Nadkarni, Nalini M; Weber, Caitlin Q; Goldman, Shelley V; Schatz, Dennis L; Allen, Sue; Menlove, Rebecca
Abstract: Scientists are increasingly motivated to engage the public, particularly those who do not or cannot access traditional science education opportunities. Communication researchers have identified shortcomings of the deficit model approach, which assumes that skepticism toward science is based on a lack of information or scientific literacy, and encourage scientists to facilitate open-minded exchange with the public. We describe an ambassador approach, to develop a scientist's impact identity, which integrates his or her research, personal interests and experiences to achieve societal impacts. The scientist identifies a community or focal group to engage, on the basis of his or her impact identity, learns about that group, and promotes inclusion of all group members by engaging in venues in which that group naturally gathers, rather than in traditional education settings. Focal group members stated that scientists communicated effectively and were responsive to participant questions and ideas. Scientists reported professional and personal benefits from this approach.